KALIMAT KONDISIONAL DALAM BAHASA ARAB Tinjauan Sintaksis - , Afnan Arummi ([Yogyakarta] : Universitas Gadjah Mada, 2012)
This research discusses the conditional sentences (al-jumlah aâsy- syarthiyyah) in Arabic according to modern linguistic consideration. A discuss which has concerns the theoretical concepts of Arabic conditional sentences, the system of syntax of Arabic conditional sentence, and the shape of Arabic conditional sentence. This research used the syntax approach to analyze the grammatical structure of Arabic conditional sentence, such as conditional indication and the relations between Arabic conditional sentence with others linguistic substance. In this case, this thesis used distributional method to analyze, to divide, and to determine the functional part of Arabic conditional sentence into the several details element. Distributional method has three steps, first: determining elements shaped Arabic conditional sentence, second: analyzing these elements according to the function and category, and third: classification of Arabic conditional sentence construct into several parts. This research concludes several main points, first: the concepts of Arabic conditional sentence equals with the concepts of conditional sentences in general linguistic. Both are describes the relation prosthesis and apodosis which connected by a conditional sign. Second: conditional sign according to Arabic terms divide to two categories particle and noun. Besides connecting two clauses, this sign influence the change verbâs declension for every clause. Functionally, the influence of sign classified into three sign they are conditional apocopate, conditional non-apocopate, and meaning apocopate. Third: Arabic conditional sentence has many constructs with processed by the element which shaped Arabic conditional sentence, such as imperative sentence, commence sentence, particle of oath, particle of interrogative, confirmative, negation, apposition, primitive verb, noun verb (interjection) and another idiom. This construction also has phase clause and ellipsis process.